The Ontology of Species: Commentary on Kasperbauer's 'Should We Bring Back the Passenger Pigeon? The Ethics of De-Extinction'. Issue 1 (2nd January 2017) - Beever, Jonathan
Abstract: Beneath important ethical questions about the impacts of de-extinct species on ecosystems and the potential harms to individual organisms lies a more fundamental assumption; namely, that the thing being "de-extinct-ed" is indeed a member of previously existing species. This is the ontological assumption: that genetic make-up of the individual is both a necessary and sufficient condition for species membership. Questioning this ontological assumption poses an even more critical challenge for de-extinction. Genes a member of a species do not make. They represent a mere necessary condition. Sufficiency entails a broad set of ecological connections, inside and out. In this commentary on Kasperbauer's target article, I argue for the primacy of ontology in the ethical analysis of de-extinction.